Interdisciplinary perspectives on business convergence, computing, and legality - Khurana, Reema, 1968-; Aggarwal, Rashmi. (A volume in the Advances in E-business research (AEBR) book series,)
"This book investigates the development of convergent and interoperable systems in business environments, with a particular focus on potential legal implications that emerge when a company begins branching out into domains traditionally occupied by suppliers and consumers"--Provided by publisher.